Assessing the Impact of a Viral Infection on the Expression of Transposable Elements in the Cabbage Looper Moth (Trichoplusia ni). (6th October 2021) - Muller, Héloïse; Loiseau, Vincent; Guillier, Sandra; Cordaux, Richard; Gilbert, Clément
Abstract: Most studies of stress-induced transposable element (TE) expression have so far focused on abiotic sources of stress. Here, we analyzed the impact of an infection by the AcMNPV baculovirus on TE expression in a cell line (Tnms42) and midgut tissues of the cabbage looper moth ( Trichoplusia ni ). We find that a large fraction of TE families (576/636 in Tnms42 cells and 503/612 in midgut) is lowly expressed or not expressed at all [≤ 4 transcripts per million (TPM)] in the uninfected condition (median TPM of 0.37 in Tnms42 and 0.46 in midgut cells). In the infected condition, a total of 62 and 187 TE families were differentially expressed (DE) in midgut and Tnms42 cells, respectively, with more up- (46) than downregulated (16) TE families in the former and as many up- (91) as downregulated (96) TE families in the latter. Expression log2 fold changes of DE TE families varied from −4.95 to 9.11 in Tnms42 cells and from −4.28 to 7.66 in midgut. Large variations in expression profiles of DE TEs were observed depending on the type of cells and on time after infection. Overall, the impact of AcMNPV on TE expression in T. ni is moderate but potentially sufficient to affect TE activity and genome architecture. Interestingly, one host-derived TE integrated into AcMNPV genomes is highly expressed in infected Tnms42 cells. This result shows that virus-borne TEs can be expressed, further suggesting that they may be able to transpose and that viruses may act as vectors of horizontal transfer of TEs in insects.